Determinants of Locating R&D Activity in the Philippines: Policy Implications - Josef T. Yap; Mari-Len R. Macasaquit; Kathrina G. Gonzales (Philippine Institute for Development Studies (PIDS), 2010)
Research and development (R&D) is an important resource for sustained economic growth. New knowledge created by a firm has spillover effects that improve the productivity of other firms and even other sectors. This is the heart of endogenous growth theory. In this framework, government policies can affect the rate of long-term economic growth by impacting the accumulation of both physical and human capital and the effort dedicated to research and development and the creation of new knowledge. A country can supplement its R&D efforts by enticing R&D firms to locate in the country or encourage local firms and multinational corporations operating there to conduct R&D activities. Factors that affect these decisions can be classified into push factors, pull factors, policy factors, and enabling factors. The last three are relevant for the host country while the first set of factors relate to the home country. A survey of firms operating in the Philippines was conducted to determine which factors are deemed important and areas where the Philippines is deemed inadequate. The findings have important policy implications. Push factors are found to be important, particularly the need to remain competitive. The pull factors that rate highly are (i) availability of talented skills at low cost; and (ii) size of market. The main policy factors that encourage firms to locate in the Philippines are: (i) good quality of education; and (ii) protection of intellectual property rights. The enabling factors are: (i) low cost of doing business; (ii) good physical and communication infrastructure; (iii) legal system; and (iv) availability of R&D support services. Two aspects are prominent in terms of discouraging R&D activity in the Philippines: (i) the high cost of R&D equipment and technology; and (ii) lack of technical manpower/engineers. Policies can look into the host country factors that do not rate highly and address the areas that are evaluated poorly. Policymakers should also be aware of the source of outward R&D spending which are mainly firms from the US and Japan. Most R&D of these firms is conducted in the ICT, automotive, and pharmaceutical industries. Meanwhile, interviews with associations of firms indicate that there is no cooperation among individual firms in terms of conducting R&D. The government can also initiate, strengthen, and support joint R&D efforts among firms in a specific sector given that there will likely be significant spillover effects in this type of endeavor.
Keywords: 330; economic growth; foreign investment; technological innovation; intellectual property rights; Philippines; outsourcing; knowledge spillover; endogenous growth theory; push and pull factors; R&D spending; R&D investment; research and development (R&D); Technischer Fortschritt; Innovation; Befragung; Philippinen